Efecto de la utilización del butirato de sodio microencapsulado en la producción de huevo de codornices (Coturnix coturnix) - Valdiviezo Vega, Karolay Estefany (2019)
The objective of this research was to determine the effect of microencapsulated sodium butyrate (BSM) on the productive variables; 64 quails of 45 days of age were evaluated and divided into 4 groups. One of the groups received the control diet and other groups with levels of 0.05%, 0.10% and 0.15% BSM supplementation for 30 days. The variables evaluated were: egg weight (PH), weight increase (ΔP), feed consumption, feed conversion (CA), mortality (%), percentage of posture (%) and economic evaluation (cost-benefit). There were no significant differences between the treatments in all the productive variables evaluated (p> 0.05), although it is clear that the diet with 0.05% of BSM exerts the best positive effects in terms of percentage of posture, egg weight, food conversion and cost - benefit. In conclusion, BSM is a potential nutritional compound to improve productive parameters.